Social Stress-Related Epigenetic Changes Associated With Increased Heart Rate Variability in Infants - Aghagoli, Ghazal; Conradt, Elisabeth; Padbury, James F.; Sheinkopf, Stephen J.; Tokadjian, Hasmik; Dansereau, Lynne M.; Tronick, Edward Z.; Marsit, Carmen J.; Lester, Barry M. (Frontiers in Behavioral Neuroscience, 2020)
Early life stress can result in persistent alterations of an individual’s stress regulation through epigenetic modifications. Epigenetic alteration of the NR3C1 gene is associated with changes in the stress response system during infancy as measured by cortisol reactivity. Although autonomic nervous system (ANS) reactivity is a key component of the stress response, we have a limited understanding of the effects of NR3C1 DNA methylation on ANS reactivity. To examine this relation, ANS stress responses of term, 4–5-month-old healthy infants were elicited using the face-to-face still-face paradigm, which involved five, 2-min episodes. Two of these episodes were the “still-face” in which the mother was non-responsive to her infant. EKG was acquired continuously and analyzed in 30 s-intervals. Cheek swabs were collected, and DNA was extracted from buccal cells. Respiratory sinus arrhythmia (RSA) was measured as heart rate variability (HRV). Mean HRV was calculated for each 30-s “face to face” episode. DNA methylation of NR3C1 was calculated using bisulfite pyrosequencing. Percent DNA methylation was computed for each of the 13 NR3C1 CpG sites. The relations between mean HRV for each “face to face” episode and percent DNA methylation was examined averaged over CpG sites 1–6 and 7–13 and at each individual CpG site. Higher HRV at baseline, first reunion, and second still-face was related to greater methylation of NR3C1 CpG sites 1–6. Higher HRV at the second reunion was related to greater methylation of NR3C1 CpG sites 12 and 13. These data provide evidence that increased methylation of NR3C1 at CpG sites 12 and 13 are associated with increased activation of parasympathetic pathways as represented by increased HRV.